Use of morphological differences for the identification of two picarel species Spicara flexuosa and Spicara maena (Pisces: Centracanthidae) - MINOS, G.; IMSIRIDOU, A.; KATSELIS, G. (Mediterranean Marine Science, 2013)
The recognition and identification of the two species of Spicara genus (Spicara flexuosa, picarel and Spicara maena, blotched picarel) is difficult, due to a systematic confusion until now. In the present work a number of external morphometric features (ten body ratios) are evaluated for their diagnostic possibilities. According to Principal Component Analysis results, the body ratios head length to standard length, head height to head length and the ratios of two body heights, indicated that these characters were not related to the maturity stage of the species. The discriminant analysis based on the above body ratios, indicated rather high level of discrimination (83.2%) of the examined samples in two species. The results are discussed, and possibilities of improvement in the identification methodology for the two species are proposed.